Identifikasi Sintaksis dalam mengukur kompetensi gramatika sesuai Standard Kemampuan Bahasa Inggris Penerbangan ICAO - Benny Kurnianto; Ahmad Rossydi; Alwazir Abdusshomad (Politeknik Penerbangan Makassar, 2022)
The structure is one of the six dimensions examined in the ICAO language proficiency test. This study aims to provide evidence on test takers’ difficulties in this area. Through the corpus mechanism, a number of interview test sessions were selected and transcribed. The grammar errors and mistakes were then analyzed under their syntactic functions. They were classified into word classes namely noun, verb, adjective, adverb, preposition, conjunction, interjection, and determiner. They were then sorted by the most frequent occurrences. This study found that the most frequent test taker’s structure problem that occurred during the IELP test was dealing with the verb with 30%. Then, the second most frequent was the noun with 22% and the third was the preposition with 16%. The study suggested that the focus related to grammar proficiency tests must be incorporated into the syllabus of English courses in aviation training. The training should be more focused on training the student on how to arrange sentences with the correct form of verb/verb phrase, noun/noun phrase, and preposition phrase.